Cognitive Regeneration and the Noetic Effects of Sin: Why Theology and Cognitive Science May not be Compatible - Launonen, Lari (European journal for philosophy of religion, 2021)
Justin Barrett and Kelly James Clark have suggested that cognitive science of religion supports the existence of a god-faculty akin to sensus divinitatis. They propose that God may have given rise to the god-faculty via guided evolution. This suggestion raises two theological worries. First, our natural cognition seems to favor false god-beliefs over true ones. Second, it also makes us prone to tribalism. If God hates idolatry and moral evil, why would he give rise to mind with such biases? A Plantingian response would point to the noetic effects of sin. Such a response, however, would have to assume that God is restoring the minds of believers. This paper considers empirical reasons to doubt that such a process is taking place.